Предмет: Математика,
автор: pavlotan3
0,6*(-9)^4+1,9*(-9)^2-4
Ответы
Автор ответа:
0
= (-9)²(0,6*81+1,9)-4=81(48,6+1,9)-4=4090,5-4=4086,5
Автор ответа:
0
1) 0,6•( -9)^4 + 1,9•( - 9)^2 = (-9)^2•( 0,6•( - 9)^2 + 1,9 ) = 81•( 0,6•81 + 1,9 ) = 81•( 48,6 + 1,9) = 81•50,5 = 4090,5
2) 4090,5 - 4 = 4086,5
Ответ 4086,5
2) 4090,5 - 4 = 4086,5
Ответ 4086,5
Похожие вопросы
Предмет: Русский язык,
автор: yana7771777yana
Предмет: Английский язык,
автор: margaret0009
Предмет: Математика,
автор: yakubauartsemi
Предмет: Алгебра,
автор: 124542555
Предмет: Математика,
автор: Klim22112002